A new genus for Sesarma (Holometopus) tangi Rathbun, 1931 (Decapoda: Brachyura: Sesarmidae) from mangrove forests, with notes on its ecology and conservation. Issue 1 (20th November 2019) - Ng, Peter K L; Shih, Hsi-Te; Cannicci, Stefano
Abstract: The poorly known sesarmid crab Sesarma ( Holometopus ) tangi Rathbun, 1931 was described from one male from Fujian, China, and was transferred to Neosarmatium Serène & Soh, 1970 by Schubart & Ng (2002) . The collection of a good series of fresh specimens from near the type locality and Hong Kong allows us to reappraise its taxonomy. The new material shows that Sesarma tangi should be referred to its own genus, differing markedly from congeners in the detailed structure of its male and female chelae as well as in the form of the male first gonopods. This conclusion is strongly supported by genetic data.